EVALUASI SISTEM PERAWATAN JALAN REL LINTAS STASIUN KUTOARJO â STASIUN TUGU - , HASTORO PAMULUNG SUMBOWO ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The railway maintenance includes railway inspection and maintenance program arrangement. The railway inspection performed as the initial action to obtain data of the railway condition. Well railway geometric condition is very necessary for safety and comfort. Traffic load or natural factor will lead to the changes in the railway shape/geometry. Deviations are permitted as long as not exceed the limits / tolerance of the railway security rules. The study was conducted on the territory of DAOP VI, Yogyakarta, in the Kutoarjo - Yogyakarta double track railway, which connects Kutoarjo Station (Km 477 +600) - Tugu Station (Km 542 +539), a distance of 64 km. Since the passing tonage result is 16,466 tons/year, so that Kutoarjo - Yogyakarta link included in the UIC IV (T = 9.8 to 17.5 million tons/year) and Second class of railway. Based on the RPT in 2008 there was no replacement for R42, wood or concrete sleeper, but the additional ballast programmed as much as 3,500 m3. Tamping needs programmed for the whole railway traffic based on the train measurement that is 1.4 times / year. The upstream of Kutoarjo - Yogyakarta track has Category 2 of TQI values (84.91%) then increasing to category 1 (63.11%) in May for the total length of the railway. The downstream track has Category 2 (72.02%) in January the increasing to 73.78% in May. Moreover, based on the analysis of human resource requirement, DAOP VI-Yogyakarta to implement the RPT program 2008 in the Kutoarjo - Yogyakarta line has employee deficiency as much as 67 people .